APOL1 risk variants and the development of HIV‐associated nephropathy. (31st December 2020) - Goyal, Rohan; Singhal, Pravin C.
Abstract : HIV‐associated nephropathy (HIVAN) remains a concern among untreated HIV patients, notably of African descent, as patients can reach end‐stage renal disease within 3 years. Two variants (G1 and G2) of the APOL1 gene, common in African populations to protect against African sleeping sickness, have been associated with an increased risk of several glomerular disorders including HIVAN, hypertension‐attributed chronic kidney disease, and idiopathic focal segmental glomerulosclerosis and are accordingly named renal risk variants (RRVs). This review examines the mechanisms by which APOL1 RRVs drive glomerular injury in the setting of HIV infection and their potential application to patient management. Innate antiviral mechanisms activated by chronic HIV infection, especially those involving type 1 interferons, are of particular interest as they have been shown to upregulate APOL1 expression. Additionally, the downregulation of miRNA 193a (a repressor of APOL1) is also associated with the upregulation of APOL1. Interestingly, glomerular damage affected by APOL1 RRVs is caused by both loss‐ and gain‐of‐function changes in the protein, explicitly characterizing these effects. Their intracellular localization offers a further understanding of the nuances of APOL1 variant effects in promoting renal disease. Finally, although APOL1 variants have been recognized as a critical genetic player in mediating kidney disease, there are significant gaps in their application to patient management for screening, diagnosis, and treatment. Abstract : The collapsing variant of focal segmental sclerosis (cFSGS), a hallmark of HIVAN, is a consequence of interferons‐mediated APOL1 expression in HIV‐infected podocytes and parietal epithelial cells (PECs). G0 facilitates PEC transition, but G1/G2 lacks this function. G1/G2 not only exacerbates HIV‐induced podocyte injury but also prevents their replacement. A gain of function in podocytes and loss of function in PECs result in the development of cFSGS in G1/G2‐HIV patients.